YIELD OF THE VARIETY OF BEAN FT BONITO IN THE COMBINATION OF SYSTEMS OF SOWING, POPULATIONS OF PLANTS AND DOSES OF NITROGEN - CÁCERES, Sixto Hugo Rabery (Scientia Agraria, 2002)
During the growing season of the 1998/99 year, four field experiment was carried out, at the Cangüiri Experiment Station of the Universidade Federal do Paraná, at Pinhais, PR, with the objective to get the best combination of crop management for dry bean yield in conventional and no tillage cropping systems. It was desired to determinate the plant population, the rows spacing, the nitrogen doses and the combination in between plant population and nitrogen doses to get better yield. The soil is classified as one Latossolo Vermelho- Amarelo Álico. In the last year, the area was cultivated with maize and oat. The experimental design utilized was a randomized complete block with 16 treatments, from the factorial arrangement of four plants population (285, 427, 570 and 712 thousands of plants) with four nitrogen doses (0, 40, 80 and 120 kg.ha-1). Two experiments were in conventional cropping system and two under no-tillage, considering 0.35 m and 0.50 m between rows and utilizing FT Bonito bean variety, an indeterminate one, type II semi-erect growth habit, cream coat color with havana list, carioca commercial group. The plots in the 0.35 m row experiment, had six rows, considering the central four as utility area, and the plots in the 0.50 m had four rows, considering the central two as utility area. The results showed that grain yield in the 0.50 m row experiments increase in the two cropping systems. It showed also that there were no significant interference of plant population neither of the nitrogen doses. The conclusion is that the plant population, to better explore the bean yield potential, is between 200 and 400 thousand plants per hectare with 0.50 m between rows, for both cropping systems.